EFL teachers’ motivational complexity and dynamics during collaborative action research - Zheng, Hongying; Huan, Tingting (Frontiers in Psychology, 2022)
Collaborative action research (CAR) is a process that brings about changes to teachers in social situations as the result of collaboration. The adoption of complexity theory, accordingly enables the examination of teachers’ motivation during the CAR from a complex and dynamic perspective, while the inclusion of self-determination theory (SDT) highlights the trajectory of teachers’ self-development. Aiming to reveal EFL teachers’ motivational complexity and dynamics during the CAR, this study investigated six EFL teachers’ motivation by conducting semi-structured interviews, observations, and reflective writings. The results indicate that EFL teachers’ motivation in the context of the CAR is complex and dynamic, which cannot be simply divided into intrinsic and extrinsic motivation. The dynamic interaction between the teachers’ psychological self and the contexts further leads to different trajectories of motivational change. Moreover, as an important source of “perturbations” promoting the teachers’ motivational change, the CAR accumulates all the possible support for teachers to meet their psychological needs in terms of competence, autonomy, and relatedness. The findings provide insights into EFL teachers’ motivation and offer useful suggestions for teachers’ professional development.